Scheduling around bottleneck resources : a scheduling approach for flexible flow lines (software system development) - Sundaramoorthy Ravikumar. (2008)
This dissertation concentrates on the critical machines first using forward, backward and ‘forward & backward’ scheduling techniques, which is a different approach from other scheduling systems commercially available. The “scheduling around bottleneck” approach aims to utilize the bottleneck machines to the maximum and leads to higher output.